Efeitos periodontais, dentoalveolares e esqueléticos da Expansão Rápida da Maxila Assistida Por Mini Implantes – MARPE - PAIXÃO, Flávia Carvalho de Oliveira (2024)
Maxillary transverse deficiency is one of the most common skeletal problems encountered in clinical practice. this condition, if not corrected promptly, can result in severe functional, periodontal, and skeletal problems. Palatal expansion assisted by mini-implants has been offered as a non-surgical and less invasive option for the treatment of this malocclusion. This study aimed to present, through a series of cases and a systematic review and meta-analysis, the effectiveness and the periodontal and dentoalveolar alterations resulting from the treatment. Three patients, female, from 3 different age groups, who had maxillary atresia associated with class II malocclusion and which were corrected using miniscrew-assisted rapid palatal expansion (MARPE) were selected. In addition, a systematic literature search was carried out to compare which treatment generates less adverse periodontal and dentoalveolar effects, Whether surgically assisted rapid palatal expansion (SARPE) or MARPE. Sixteen studies were selected for the systematic review and among them, six were eligible for the meta-analysis. Within the limitations of these studies, we can suggest that MARPE is an effective treatment for correcting transverse maxillary deficiency associated with Class II malocclusion in skeletally mature patients. Furthermore, when literature was searched, the treatment showed less thickness reduction buccal bone and less inclination of the device's supporting teeth when compared to surgical expansion.